Qualidade de pellets de bagaço de cana-de-açúcar e serragem de eucalipto em diferentes composições - Oliveira, Bárbara Mendes de (2016)
The use of agroforestry biomass in pellets form for energy purposes, besides being an alternative for production of clean energy, is an option for the disposal of lignocellulosic residues. This work evaluated the quality of pellets produced with sugarcane bagasse and eucalyptus sawdust in different compositions. For each composition, originating from the pellets, the total extractives contents, total lignin, moisture, bulk density, ash, lower calorific value and energy density were determined. In the pellets, in different proportions, were realized the analyzes of moisture, bulk density, compaction rate, ash content, lower calorific value, volatile material content, fixed carbon, energy density, combustion temperature and physical and mechanical characteristics (diameter, length, unit density, diametric compression strength, fines content and mechanical durability). Sugarcane bagasse and eucalyptus sawdust individually and in composite form presented desirable characteristics for energy use through of the pelletizing process. The results were satisfactory for almost all the properties studied, except bulk density and mechanical durability for the pellets between 100% and 70% sugarcane bagasse in their constitutions.